Assessment of specific contribution of residual stress generated near surface anomalies in the high temperature fatigue life of a René 65 superalloy. Issue 1 (17th May 2016) - Gourdin, S.; Cormier, J.; Henaff, G.; Nadot, Y.; Hamon, F.; Pierret, S.
Abstract: This study evaluates the influence of residual stresses induced by the fabrication of surface anomalies on the fatigue crack growth in a nickel based superalloy. To separate the notch effect of the geometry from the residual stress field induced by fabrication of the surface flaws, two V‐type anomalies are considered: scratches and dents with equivalent morphology and size. A specially designed heat treatment has been used to reduce the magnitude of residual stresses around these anomalies in order to highlight their effects on the different stages of the crack propagation, under low cycle fatigue conditions at 400 °C. The crack initiation life is short for both anomalies but in the presence of compressive residual stresses, a decrease of the fatigue crack growth rate has been observed during the first stages of the crack propagation. Furthermore, the results showed that without residual stresses, scratches and dents exhibit the same behaviour. Thus, the residual stress field below surface anomalies is the main parameter controlling the fatigue life from surface anomalies.